THE IMPACT OF DIGITAL TRANSFORMATION ON THE FINANCIAL PERFORMANCE OF COOPERATIVES IN SURABAYA - Samsiyah, Siti; Arianto, Bisma; Firdausia, Yuli Kurnia; Seven, Fiorella (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The digitalization of cooperative services aims to provide convenience, speed, comfort, and security in transactions for cooperative members. Improved financial performance reflects good financial health. When a process is evaluated and monitored periodically, the results will reflect its performance. This study aims to determine how the digitalization of services affects the financial performance of cooperatives in Surabaya. The method used in this research is descriptive research with a quantitative approach. The research sample consists of financial reports produced by cooperatives that have adopted service digitalization. The results show that digitalization of services affects financial performance (ROA, ROE, NIM). Digitalization of services has a significant impact on the financial performance of cooperatives, which has developed along with technological advancements. This research is limited to the Surabaya area, so the results may not be applicable to cooperatives in other regionsKEYWORDS: Accounting, Digitalization, Financial Performance, Cooperatives, Services